2017
DOI: 10.1021/acsmedchemlett.7b00247
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Allosteric Site of Oncoprotein BCR-ABL as an Alternative Strategy for Effective Target Protein Degradation

Abstract: Protein degradation technology based on hybrid small molecules is an emerging drug modality that has significant potential in drug discovery and as a unique method of post-translational protein knockdown in the field of chemical biology. Here, we report the first example of a novel and potent protein degradation inducer that binds to an allosteric site of the oncogenic BCR-ABL protein. BCR-ABL allosteric ligands were incorporated into the SNIPER (Specific and Nongenetic inhibitor of apoptosis protein [IAP]-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 32 publications
1
91
0
3
Order By: Relevance
“…Consistent with the degradation of BCR-ABL protein, SNIPER(ABL)-39 inhibited the signaling pathways initiated by BCR-ABL, and suppressed the growth of BCR-ABL-positive CML cells. 30) These results suggest that SNIPER(ABL)-39 could be a lead as a degradation-based novel anti-cancer drug against BCR-ABL-positive CML.…”
Section: Development Of a Potent Degrader Against Bcr-abl Sniper(abl)mentioning
confidence: 85%
See 3 more Smart Citations
“…Consistent with the degradation of BCR-ABL protein, SNIPER(ABL)-39 inhibited the signaling pathways initiated by BCR-ABL, and suppressed the growth of BCR-ABL-positive CML cells. 30) These results suggest that SNIPER(ABL)-39 could be a lead as a degradation-based novel anti-cancer drug against BCR-ABL-positive CML.…”
Section: Development Of a Potent Degrader Against Bcr-abl Sniper(abl)mentioning
confidence: 85%
“…To improve the protein knockdown activity, we tested various combinations of ABL inhibitors and IAP ligands, and the linker was optimized for protein knockdown activity of SNIPER(ABL). 30) The resulting SNIPER(ABL)-39 (Table 1), in which dasatinib is conjugated to LCL161 derivative by polyethylene glycol ×3 linker, shows potent activity. At 10 nM, SNIPER(ABL)-39 induced dramatic reduction of BCR-ABL protein in CML cell lines such as K562 and KU812.…”
Section: Development Of a Potent Degrader Against Bcr-abl Sniper(abl)mentioning
confidence: 99%
See 2 more Smart Citations
“…Pioneering studies by the Crews lab have shown that BCR-ABL PROTACs, consisting of CRBN or VHL recruiters linked to BCR-ABL ATP binding pocket-targeting kinase inhibitors such as dasatinib and bosutinib or allosteric inhibitors such as GNF-2, showed preferential degradation of c-ABL over modest degradation of BCR-ABL (Burslem et al, 2019;Lai et al, 2016). Notably, this work has spurred development of various degradation strategies targeting BCR-ABL (Demizu et al, 2016;Shibata et al, 2017Shibata et al, , 2019Shimokawa et al, 2017;Zhao et al, 2019). In this study, we aimed to determine whether our recently discovered covalent RNF114 recruiter nimbolide could be used to kinase-targeting PROTACs, and if so, whether differential selectivity in degrading BCR-ABL, compared to similar BCR-ABL PROTACs employing VHL or CRBN could be attained.…”
Section: Main Textmentioning
confidence: 99%